Factores sociodemográficos y sexuales asociados al conocimiento sobre VIH sida en adolescentes de la Institución Educativa “Juan Jiménez Pimentel” – Tarapoto. Abril – julio. 2013 - Acuña Tello, Lorena Del Carmen (2013)
This study aimed to determine the relationship between demographic factors and sexual knowledge about HIV / AIDS among adolescents from the Educational Institution "Juan Jimenez Pimentel", sociodemographic factors determining adolescents, determining adolescent sexual factors, determine the level of knowledge about HIV / AIDS, identify whether the demographic factor is significantly associated with knowledge of HIV / AIDS and to identify whether the sexual factor is significantly associated with knowledge of HIV / AIDS. A Quantitative study type, because it starts with preconceived ideas about sex and sociodemographic factors. The sample was obtained by simple random sampling consisting of 196 adolescents selected inclusion criteria, with a confidence level of 95%, the technique used in the study was the survey and the survey instrument. According to the objectives is obtained the following results: Of 196 adolescents (48.5%) 95 students, were aged between 10-13 years (Early Childhood), (39.8%) 78 adolescents aged 14 to 16 years (Age Media) and (11.7%) 23 adolescents 17-19 years (Age Delayed), 52.6%), 103 were male and sex (47.4%) Female sex 93 (71.4%) 140 Low grade adolescents were study and (28.6%) High Grade 56 adolescents Study, (69.4%) 136 adolescents and professed the Catholic religion (25.5%) 50 Evangelical Religion and adolescents (5, 1%) 10 professed other religions, 96.4%) presented 189 background and adolescents (3.6%) 7 adolescents were STI history (56.1%) had 110 adolescents Sexual Couple (41.8% ) 82 adolescents had a couple Single Sexual and (2%) 4 teenagers had multiple sexual partners (56.6%) 111 adolescents do not use condoms, while (43.4%) 85 teenagers if you use condoms, 84.7%) Adequate Knowledge adolescents had 166, while (15.3%) adolescents had 30 Inadequate Knowledge. Concluding that adolescents generally have adequate knowledge about HIV / AIDS, to obtain a significance level <0.005 THROUGH inferential statistics chi square, so there is statistical association between sociodemographic factors and sexual knowledge about HIV / AIDS, teen educational institution Juan Jimenez Pimentel-Tarapoto